A predictive diatom-based model to assess the ecological status of streams and rivers of Northern Spain. (July 2018) - Pardo, Isabel; Delgado, Cristina; Abraín, Rut; Gómez-Rodríguez, Carola; García-Roselló, Emilio; García, Liliana; Reynoldson, Trefor B.
Graphical abstract: Highlights: A new predictive model to assess the ecological status of rivers of Northern Spain. 4 river types identified were based on their diatom reference communities. Logistic multinomial Model was used to assign test sites to a river type. Ecological Quality Ratios estimated from floral similarity with type biological references. Diatoms responded significantly to eutrophication and intensive agriculture. Abstract: In this study we developed a predictive diatom-based model to assess the ecological status of streams and rivers of Northern Spain. Diatom samples were collected with standard protocols over stones from 676 sites distributed along existing environmental conditions across Northern Spain, during seven years between 2002 and 2008 (n = 1056 samples). This dataset included a network of 91 reference sites selected by using criteria that confirmed the absence of relevant human pressures according WFD. A multinomial logistic regression using GAAC cluster-derived reference sites group as response variable was performed. The independent variables included obligatory typology factors (WFD System A typology descriptors), and other optional typology B descriptors were included in the model performed on a forward stepwise procedure. The Ecological Quality Ratios (EQRs) were obtained by dividing the observed similarity between the diatoms composition in each sample by the expected median similarity of each type reference diatom community. The model predictions (EQRs) responded significantly to eutrophication and intensive agriculture pressures, but were not related with sewages, hydromorphological alterations and extensive agriculture pressures. These results demonstrated the accuracy of the diatom model in predicting nutrient enrichment in Northern Spanish rivers and streams.